Utilizing Wordwall Puzzles as Teaching Materials for Theme 3 in Fifth Grade - Windiyani, Tustiyana; Sofyan, Deddy; Novita, Lina; Patricia, Regina (Jurnal Prima Edukasia, 2024)
Technology serves a crucial role in supporting teachers as a valuable teaching tool. Class activities require engaging and creative teaching materials that can motivate students to actively participate in the learning process. The study aims to develop educational materials in the form of puzzles using Wordwall, with the goal of enhancing students' creativity and promoting effective learning. A Research and Development (R&D) approach was utilized to create puzzle products using Wordwall. An experimental design was then implemented to examine the impact of using puzzle teaching materials from Wordwall on reading literacy, creativity, and learning outcomes. The product's viability was assessed by media and materials experts. Following an assessment of its viability, a small-scale product trial was conducted with a group of 10 students, followed by a larger-scale test involving 32 students. A study discovered the practicality and efficiency of the product for implementation in primary schools. The findings of this study suggest that utilizing wordwall puzzles media in theme 3 material is both practical and beneficial for facilitating learning. According to this, the research findings can serve as a valuable teaching strategy for educators to effectively guide their students. This research can serve as an effective strategy for teachers to support and guide students in their learning.